2020
DOI: 10.1111/pce.13739
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of organ‐autonomous expression of Arabidopsis circadian oscillators

Abstract: The circadian pacemaker in plants is a hierarchical multioscillator system that directs and maintains a 24-hr oscillation required for organism homeostasis and environmental fitness. Molecular clockwork within individual tissues and organs acts cell autonomously, showing differences in circadian expression of core oscillators and their target genes; there are functional dominance and coupling in the complex regulatory network. However, molecular characteristics of organ-specific clocks are still unknown. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Previous studies have shown that the oscillation in the roots fell behind that in the shoots with a longer period and slower peak expression in A. thaliana (James et al, 2008;Takahashi et al, 2015;Li et al, 2020). Based on these…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Previous studies have shown that the oscillation in the roots fell behind that in the shoots with a longer period and slower peak expression in A. thaliana (James et al, 2008;Takahashi et al, 2015;Li et al, 2020). Based on these…”
Section: Resultsmentioning
confidence: 85%
“…These two pathways are tightly coupled to modulate tissuespecific circadian rhythms, which might be necessary for the adaptation of different organs to their microenvironments. The rhythmicity pathway is regulated by the circadian clock and environmental fluctuations, and the tissue-specific pathway may be affected by protein-protein interactions, chromatin interactions, and alternative promoter usage (Yeung and Naef, 2018;Li et al, 2020). Transcription factors can modulate tissue-specific gene expression by interacting with local cofactors in different tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations